Accuracy order in L2 grammatical morphemes: Corpus evidence from different proficiency levels of Turkish learners of English - Akbaş, Erdem; Ölçü-Dinçer, Zeynep (Studies in Second Language Learning and Teaching, 2021)
The present study empirically scrutinizes the fixed natural order of grammatical morphemes relying on a manual analysis of an EFL learner corpus. Specifically, we test whether the accuracy order of L2 grammatical morphemes in the case of L1 Turkish speakers of English deviates from Krashen’s (1977) natural order and whether proficiency levels play a role in the order of acquisition of these morphemes. With this in mind, we focus on the (in)accuracy of nine English grammatical morphemes with 2883 cases manually tagged by the UAM Corpus Tool in the written exam scripts of Turkish learners of English. The results based on target-like use scores provide evidence for deviation from what is widely believed to be a set order of acquisition of these grammatical morphemes by second language learners. In light of such findings, we challenge the view that the internally driven processes of mastering grammatical morphemes in English for interlanguage users are largely independent of their L1. Regardless of L2 grammar proficiency in our data, the observed accuracy of some morphemes ranked low in comparison with the so-called natural order. These grammatical morphemes were almost exclusively non-existent features in participants’ mother tongue (e.g., third person singular –s, articles and the irregular past tense forms), thus suggesting the influence of L1 in this respect.